Evolutionary Genetics of Invasive Mammal Species Introduced in Argentina - Lizarralde, Marta Susana (2018)
Evolutionary genetics of invasive species has been unexplored in Argentina. Invasive alienspecies (IAS) have a wide geographical distribution, characteristic life cycles and great abilityto adapt, establish and spread in a new environment. Recent advances in novel moleculartechnologies, the use of higher resolution genetic markers, and the research development ongenetic variation of invasive species consolidated the importance of genetic aspects in theinvasion process. Undoubtedly, the growing concern for the disturbances generated by invasivespecies on biodiversity and functioning of ecosystems was also determinant for theinclusion of the Invasion Biology within the broad field of Evolutionary Biology includingrelevant examples that address the evolutionary genetic aspects of biological invasions. Recentstudies suggest that the invasion success of many species depends on their ability torespond to natural selection. Although the number of invasive species registered in Argentinafar exceeds 600, little research has been done on invasive mammal species and only fiveof them were hitherto genetically analyzed. Presuming that invasion genetics is incorporatedinto the agenda of control and management organizations, it would allow integrating theecological, genetic, and evolutionary biology aspects for knowledge of invasive specieswidely distributed in Argentina. The objective of this article is to highlight the importanceof evaluating the genetic structure of invasive species for their management and to informabout the invasive species of mammals that were introduced in Argentina and have been orare being analyzed genetically.